Effect Of Different Hybrids*Spacing*Fertilizer Doses On Vegetative And Yield Characters Along With Correlation Among The Characters In Broccoli (Brassica Oleracea Var. Italica L.) - Thakur, Priya; Saurabh, Amit; Bisht, Yashpal Singh; Rawat, Anand Singh; Ahir, Megha; Kumar, Deepak; Kumar, Atin; Sachan, Sharad; Khan, Ruksana; Sharma, Vedika; et al. (Journal of Neonatal Surgery, 2025)
The study was carried out to examine the effect of different hybrids*spacing*fertilizer doses on vegetative and yield characters along with correlation among the characters in broccoli (Brassica oleracea var. italica L.) at Department of Horticulture, Eternal University, Baru Sahib, Sirmaur (Himachal Pradesh). The experiment was laid out in Factorial Randomized Block Design with three replications. The experiments comprised of three hybrids (Saki, Diana, Besty), three levels of spacing (60 × 30 cm, 60 × 45 cm and 60 × 60 cm) and three different fertilizer doses (75% RDF, 100% RDF, 125% RDF). Results revealed that maximum plant height (67.80 cm, 70.40 cm, 69.10 cm) was recorded from treatment combination H3S1F3, highest curd yield/m2 (4.77 kg, 5.22 kg, 4.99 kg) was produced under H2S1F3 and H2S3F3 found maximum number of leaves per plant (19.73, 26.07, 22.90). Whereas, treatment combination H3S3F3 recorded maximum plant spread (91.13 cm, 95.10 cm, 93.12 cm), maximum leaf area (487.96 cm2, 497.04 cm2, 492.50 cm2), stem girth (8.77 cm, 13.03 cm, 10.90 cm) and stem diameter (4.96 cm, 5.37 cm, 5.16 cm) in both the years and pooled analysis. Correlation studies revealed that different characters were highly significant at 1% and 5% level of significance. Hence treatment combination H2S1F3 must be recommended to the farmers.